Ornament and order : graffiti, street art and the parergon - Schacter, Rafael (Architecture., 2014)
Based on an in-depth ethnographic study working with some of the world's most influential Independent Public Artists, this book takes a completely new approach. Placing these illicit aesthetic practices within a broader historical, political, and aesthetic context, it argues that they are in fact both intrinsically ornamental (working within a classic architectonic framework), as well as innately ordered (within a highly ritualized, performative structure). Rather than disharmonic, destructive forms, rather than ones solely working within the dynamics of the market, these insurgent images are.